2012
DOI: 10.1124/jpet.111.183947
|View full text |Cite
|
Sign up to set email alerts
|

Selective Glucocorticoid Receptor Agonists for the Treatment of Inflammatory Bowel Disease: Studies in Mice with Acute Trinitrobenzene Sulfonic Acid Colitis

Abstract: Despite being a mainstay of inflammatory bowel disease (IBD) therapy, glucocorticoids (GCs) still carry significant risks with respect to unwanted side effects. Alternative drugs with a more favorable risk/benefit ratio than common GCs are thus highly desirable for the management of IBD. New and supposedly selective glucocorticoid receptor (GR) agonists (SEGRAs), with dissociated properties, have been described as promising candidates for circumventing therapeutic problems while still displaying full beneficia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 41 publications
4
33
0
2
Order By: Relevance
“…Our results show that CpdA moderately ameliorated signs of arthritis, including the disease activity score and the T cell response, but to a weaker extent as DEX. This is in line with previous findings indicating that CpdA diminishes parameters of the Th1 immune response and reduces inflammation (26,27). However, it should be noted that DEX was more efficient in suppressing inflammation as evident by the lower paw temperature and the smaller extent of cellular infiltrates in the synovium and cartilage damage.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Our results show that CpdA moderately ameliorated signs of arthritis, including the disease activity score and the T cell response, but to a weaker extent as DEX. This is in line with previous findings indicating that CpdA diminishes parameters of the Th1 immune response and reduces inflammation (26,27). However, it should be noted that DEX was more efficient in suppressing inflammation as evident by the lower paw temperature and the smaller extent of cellular infiltrates in the synovium and cartilage damage.…”
Section: Discussionsupporting
confidence: 80%
“…However, our data suggest that CpdA exerted adverse effects on the gastrointestinal (GI) tract and that those effects may depend on an increased rate of apoptosis in the colonic tissue (data not shown). Similar side effects were reported by Reuter et al (26), who also showed an increased apoptosis rate in colonic tissue after CpdA treatment. In contrast to CpdA, the second tested SEGRA in that study, ZK216348, did not reveal apoptosis-inducing effects, indicating that this is a CpdA-specific trait (26).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations